??lvaro Vieira Pinto, o fil??sofo do terceiro mundo: constru????es te??ricas sobre ???consci??ncia??? e ???educa????o??? - Cardoso, N??bia Luiz (2017)
The aim of this study was to analyse the education conception present in ??lvaro Vieira Pinto (1909-1987) thoughts, educator and Brazilian philosopher, who had a preoccupation in search for a national identity that should be formed by Brazilian people conscience and, more specifically, a critical conscience formed by popular classes. He still looked for the construction of a national character of an education, which still prevail a critical conscience. The methodology of this research was constructed with a qualitative approach, utilizing a bibliography revision. The proceedings to the analyses were made with the sense of comprehending the binomial ???Education and Conscience??? presented on the cutting out of this research, where the principles were aligned up with the methodologies conceptions of the researched philosopher. The actuality and the relevance of the proposal discussions by Vieira Pinto, since the decade of 1950 have been showed present still, whereas Brazil still brings education characteristics of a colonizer conscience. The practice and pedagogies conceptions are still consolidated in a naive conscience. The results of this study, after finishing the categorizations proceedings, had pointed to six controversies aspects that converge to the naive conscience concept ??? alienation, disciplinarization, conditioning, psychometrization, linearity and the logic of grade ??? and an aspect to the critical conscience concept ??? social participation. The systematization of these aspects has brought new worries, suggested to future studies. Finally, it is understood, that the teachings left by him, still make presence in the actuality, whereas the wish for an education with national identity maintain it firm, fallowing a live process of search.